Peran Komunikasi Dalam Penyelesaian Konflik - Khairuman, Muhammad Farhan; Azwardi, Azwardi; Nurdahyanti, Nurdahyanti; Simangunsong, Arimbi Syahkila (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2024)
This study aims to describe the role of communication in conflict resolution using a qualitative approach. The data sources used in this study are literature study sources that include references from journals, books and other articles. Conflicts often arise due to differences in views, interests, or values ??between individuals or groups. Communication serves as a tool to identify, understand, and resolve these differences, thereby creating mutually beneficial solutions. Using a qualitative approach, this study explores various communication strategies, such as open dialogue, mediation, and negotiation, which can increase mutual understanding and reduce tension. The results of the study indicate that effective communication can strengthen interpersonal relationships, build trust, and create an environment conducive to conflict resolution. In conclusion, communication is not only a tool for conflict resolution, but also an important means of preventing future conflicts.